FAKTOR – FAKTOR PENOPANG KETAHANAN UMKM PASCA PANDEMI COVID-19 DI INDONESIA: TINJAUAN ARTIKEL TERKINI - Oktaga, Andreas Tigor; Kasidi; Riyono (Jurnal Ilmiah Ekonomika & Sains, 2024)
The COVID-19 pandemic has significantly affected various economic sectors, especially micro, small and medium enterprises (MSMEs) in Indonesia, which are the backbone of the economy. This study aims to investigate the factors that support the resilience of MSMEs after the pandemic by reviewing recent article from 2021 to 2024. Using a critical appraisal method, the research synthesizes findings from selected articles to highlight key strategies that enable MSMEs to adapt and thrive in a challenging environment. The findings indicate that factors such as digital technology adoption, innovative marketing strategies, creativity, religiosity, collaboration, financial support, and community engagement play a critical role in enhancing MSMEs resilience. The implications of these findings suggest that MSMEs should leverage these elements to improve competitiveness and sustainability, while policymakers can formulate effective strategies to support MSMEs recovery and growth in the post-pandemic era.